Nutrient utilization in crossbred heifers fed finger millet (Eleucine coracana) straw with different proportions of bran and supplemented with different levels of groundnut-cake and cottonseed-cake - PRASAD, C S; SAMPATH, K T; SHIVARAMIAH, M T; SHIVAKUMAR, N; RAO, A SUBBA (The Indian Journal of Animal Sciences, 2013)
Crossbred heifers (36) were distributed equally under 6 treatment groups and offered finger millet straw (Eleucine coracana) and wheat bran in the ratio of 75 :25 (group 1) supplemented with groundnut- cake (GNC) at 2 levels of 15 and 30 g rumen degradable nitrogen (RDN)/kg digestible organic matter (DOM)(groups 2,3) and one level of cotton seed- cake (15g RDN/kg DOM) (group 4) and finger millet straw: wheat bran in the ratio of 60:40 (group 5) supplemented with 1 level of GNC (15g RDN/kg DOM) (group 6). The total dry matter intake (TDMI) did not differ significantly between different levels of supplement within the same levels of straw: bran fed groups. The organic matter digestibility (OMD) were significantly higher in the groups fed straw: bran (75:25) and supplemented with 2 levels ofGNC as compared to CSC supplementation and unsupplemented groups. GNC supplementation to 60:40 straw: bran ratio had no significant effect on nutrient digestibility as compared to supplementing 75:25 straw: bran groups. Increasing the proportion of wheat bran to finger millet straw did not show any improvement in diet digestibility. Also there was no significant difference between the 2 levels of GNC supplement’(15 and 30 g RDN/kg DOM) on nutrient utilization. Supplementing 15 g RDN/kg DOM through GNC to a diet ofFMS : bran (75:25) was better in terms of improving digestibility of nutrients and economics of feeding.